Pulmonary Arteriovenous Malformation Unmasked by Pregnancy: A Review of Pulmonary Arteriovenous Malformations and Cardiovascular and Respiratory Changes in Pregnancy - Anita Lukic; Larisa Cmelak; Dominik Draženović; Hrvoje Kojundzic; Ivan Kresimir Lukic; Vicko Gluncic (Case Reports in Pulmonology)
Pulmonary arteriovenous malformations are abnormal, direct communications between the branches of the pulmonary artery and pulmonary veins, but without pulmonary capillaries between them. During pregnancy, PAVMs can enlarge and become symptomatic, causing even serious complications like haematothorax. To recognize the PAVM that becomes symptomatic in pregnancy, one must be able to distinguish the patient’s symptoms caused by developing complications of PAVM, as in the case we present, from physiological changes accompanying a healthy pregnancy, including their degree in relation to the stage of pregnancy. The modified early obstetric warning score charts are a very helpful tool in the assessment of (ab)normal signs and symptoms in pregnant women, especially for physicians who rarely manage pregnant women.